Expressions of Individualization on the Internet and Social Media: Multigenerational Focus Group Study - Mayer, Gwendolyn; Alvarez, Simone; Gronewold, Nadine; Schultz, Jobst-Hendrik (JMIR Publications, 2020)
BackgroundGrowing individualization within the past decades has been described as a fundamental shift in society. Studies have reported how the digital age promotes new forms of individualism with self-tracking technologies and self-presentation in social networks. Potential harmful effects on the mental health of young adults have already been at the forefront of research. However, 2 questions that remain unanswered are how emotional experiences and expressions of self-relatedness differ among generations in their usage of the internet and social media, and if an increasing individualism can be observed by this. ObjectiveThe aim of this study is to examine whether the use of the internet and social media has led people to be more concerned about themselves than former generations. The potential consequences of mental and emotional distress among different age groups are analyzed. MethodsA focus-group approach was chosen to study the following age groups: Baby Boomers (those born in 1950-1965), Generation X (those born in 1966-1980), and Digital Natives (those born in 1981-2000). We organized 6 focus groups with 36 participants who discussed their private usage of the internet and social media, different devices, platforms and functions, communication behavior, and self-tracking. We applied inductive category formation and followed the Standards for Reporting Qualitative Research (SRQR) checklist. ResultsWe found differences in the 3 studied generations regarding the reasons for their use of the internet and social media, the effects of this use, personal feelings and experiences, expressions of self-relatedness, and social relationships. The Baby Boomers voiced a wish to stay autonomous while being in contact with their personal network. Generation X included enthusiastic members who appreciate self-tracking for curiosity and fascination, as well as people who felt fears about data surveillance. The Digital Natives reported a wish to optimize their own body by self-tracking while being faced with norms and expectations that were communicated via the internet and social media. ConclusionsAll generations expressed self-relatedness, yet by different means. The Baby Boomers expressed less individualism than Generation X and the Digital Natives, who felt the highest strain due to social comparisons. However, all generations reported specific, potentially problematic consequences for their mental health. Age-specific coping strategies are necessary to promote a mentally healthy way of using the internet and social media.